4 × 2 Tbit/s superchannel self‐coherent transmission based on carrier tracking and expanding. Issue 3 (1st January 2014) - Xiao, Xiao; Yang, Qi; Yi, Xingwen; Yang, Chao; Li, Zhaohui; He, Zhixue; Luo, Ming; Gui, Tao; Li, Chao; Zhang, Xu; Xue, Daojun; Hu, Rong; et al.
Abstract : A novel superchannel transmission scheme is proposed where an optical comb source is used to carry the multiband signal and one subcarrier is reserved for regeneration as a local oscillator at the receiver end. By combining carrier tracking and carrier expanding, a 4 × 2 Tbit/s superchannel wavelength division multiplexed self‐coherent transmission over a 320 km standard single mode fibre has been successfully demonstrated.